Effects of carnosine and anserine supplementation on relatively high intensity endurance performance - Maemura, H.; Goto, K.; Yoshioka, T.; Sato, M.; Takahata, Y.; Morimatsu, F.; Takamatsu, K. (International Journal of Sport & Health Science, 2006)
The purpose of this study was to investigate the effects of long-term chicken breast extract (CBEX) supplementation, a rich source of carnosine and anserine, on relatively high intensity endurance performance. Sixteen healthy male subjects were divided into CBEX group (n = 8) and placebo group (n = 8). The CBEX group was orally administered 200 ml CBEX drink which contained 4g of carnosine and anserine per day for 30 days. The placebo group was orally administered 200ml the same taste CBEX drink which contained no carnosine and anserine. Before and after the ingestion period, the subjects performed three sessions of consecutive endurance exercise (first session: 30-min at 50%O2max; second session: 15-min at 75%O2max; third session: until exhaustion at 100%O2max) to measure exercise duration time at 100%O2max, blood lactate concentration and ratings of perceived exertion (RPE) during the three sessions of consecutive endurance exercise. The exercise duration time at 100%O2max was significantly increased after supplementation in the CBEX group. Blood lactate concentration and RPE at 75%O2max was significantly decreased after supplementation in the CBEX group. These results suggest that the long-term ingestion of carnosine and anserine could enhance muscle buffering capacity, and in turn improve relatively high intensity endurance performance such as the so-called "last spurt" resulting from attenuation of the muscle fatigue at submaximal exercise.